The Effectiveness of the “Father-Supportive Breastfeeding” Program on Readiness of Breastfeeding Mothers - Rezeki, Sri; Siregar, Erin Padilla; Siregar, Amelia Erawaty; Simanjuntak, Emma Dosriamaya Noni Br; Damanik, Nopalina Suyanti; Simanjuntak, Parningotan; Sinuhaji, Lidya Natalia Br (Griya Eka Sejahtera, 2026)
Background: Exclusive breastfeeding (ASI) during six month First life still become standard gold in nutrition baby who is not replaced by products whatever. Globally, the latest data show There is increase, number exclusive breastfeeding still 48%, which means more from half babies in the world do not get right optimal nutrition. Failure in exclusive breastfeeding play a role to height number death baby consequence infection channel respiratory and diarrheal diseases in low- income countries low and middle.Methods: Type of research This is observational with cross-sectional design. sample with use total sampling technique. Sample data obtained through questionnaire. Research carried out in Bangun Rejo Village with with sample is all fathers who have baby age 6–12 months with total number of 40 people. Sampling technique sample using total sampling. Instrument study in the form of questionnaire closed which has been tested validity and reliability. Data were analyzed using the Chi-square test with level significance 0.05Results: Based on table on can seen the majority of 16 respondents (40%) were less Ready breast-feed with good breastfeeding fathers and minorities readiness breast-feed as many as 7 respondents (17.5%) with beastfeeding father is good. Statistical test results with using the chi square test, obtained result 0.014 < α = 0.05, can concluded There is effectiveness of the “Father-Supportive Breastfeeding” Program on readiness Mother breastfeeding. Important factors that influence success breastfeeding is one of them is readiness a mother. Readiness Mother for the breastfeeding process, attitudes and behavior Mother is part from maturity Mother in decide as well as prepare before provide exclusive breastfeeding.Conclusion: Father-Supportive Breastfeeding Program effective in increase success of exclusive breastfeeding in mothers breastfeeding, so that father involvement through support emotional, informational, and instrumental evidence contribute to increasing success Mother in maintain exclusive breastfeeding until baby aged six month. Father's support plays a role important in increase breastfeeding self-efficacy mother, reduce stress during the postpartum period, as well as create environment conducive family for practice breastfeeding. A program that is special targeting capable fathers strengthen the role of the father as an integral part of system support breastfeeding, not only as companion passive, so that impact evident in behavior breast-feed Mother.